2009
DOI: 10.1267/ahc.09021
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-5 Contributes to Microfibril Assembly in Human Periodontal Ligament Cells

Abstract: The elastic system fibers comprise oxytalan, elaunin and elastic fibers, which differ in their relative microfibril and elastin content. Human periodontal ligaments (PDL) contain only oxytalan fibers (pure microfibrils) among them. Since fibulin-5 regulates the organization of elastic fibers to link the fibers to cells, we hypothesized that fibulin-5 may contribute to the formation of oxytalan fibers. We used siRNA for fibulin-5 in PDL cell culture to examine the extracellular deposition of fibrillin-1 and -2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…An ultrastructural study of EMILIN-1 immunolocalization revealed that the molecule was clearly labeled in oxytalan fibers of the corneal stroma [13]. Moreover, based on the fact that EMILIN-1 can bind with fibulin-5, which is expressed on oxytalan fibers in our PDL culture model [15,16], we hypothesized that EMILIN-1 might contribute to the formation of oxytalan fibers in PDL. In the present study, we used a culture model of pure microfibrils to investigate the role of EMILIN-1 in the development of oxytalan fibers and found that EMILIN-1 colocalizes with oxytalan fibers and regulates their biogenesis.…”
Section: Introductionmentioning
confidence: 88%
“…An ultrastructural study of EMILIN-1 immunolocalization revealed that the molecule was clearly labeled in oxytalan fibers of the corneal stroma [13]. Moreover, based on the fact that EMILIN-1 can bind with fibulin-5, which is expressed on oxytalan fibers in our PDL culture model [15,16], we hypothesized that EMILIN-1 might contribute to the formation of oxytalan fibers in PDL. In the present study, we used a culture model of pure microfibrils to investigate the role of EMILIN-1 in the development of oxytalan fibers and found that EMILIN-1 colocalizes with oxytalan fibers and regulates their biogenesis.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, FBLN5, as a multifunctional glycoprotein, belongs to the fibulin family that has been reported to have a relationship with elastic system fibers, and contributes in assembly and organization of the extracellular matrix and regulation of microfibril formation (16)(17)(18). Decreased excretion of FBLN5 that is also known as fibulin-5 in IgA nephropathy patients compared with healthy individuals indicates the impairment of elastic system fibers and extracellular matrix (ECM)-cell interaction in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Fibulin-5 is the principle molecule involved in the control of elastic fiber formation [11,12]. We have shown previously that fibulin-5 becomes localized on oxytalan fibers and controls their rate of formation [13], and also that fibulin-5 is essential for coalescence of oxytalan fibers in PDL cell culture [10]. However, it is still unclear about the existence of LTBP-2 and the relation between fibulin-5 and LTBP-2 in periodontal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Fibulin-5 is also known to be a crucial molecule in the control of elastic fiber formation [11,12]. We have shown previously that fibulin-5 is localized on oxytalan fibers and controls the rate of their formation [13]. Fibulin-5 performs various functions by interacting with certain microfibril-associated molecules [14,15].…”
Section: Introductionmentioning
confidence: 99%